Economic And Social Analysis Of Productive Activities Of Multi-Branch Farms - Baikhanov Bahadirjon Tursunbaevich (International Journal on Integrated Education, 2022)
The article provides an economic and social analysis of the productive activities of multi-sector farms. It was noted that the theoretical and methodological organization of the functional capabilities of a multi-branch farm depends on the effectiveness of certain tasks, taking into account the general functions of agricultural development operating in certain regions. Conclusions were drawn by analyzing the results of the establishment of multi-sectoral farms in the Republic of Uzbekistan, the socio-economic situation of the regions and some of its rural areas.